1996
DOI: 10.1116/1.589136
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin probe force microscopy for characterization of semiconductor devices and processes

Abstract: Kelvin probe force microscopy was applied to the characterization of Al 0.3 Ga 0.7 As/GaAs multilayer structures and Si-pn structures. The spatial resolution of Kelvin probe force microscopy measurement was investigated using cleaved Al 0.3 Ga 0.7 As/GaAs structures. A 40-nm-thick Al 0.3 Ga 0.7 As layer was resolved with potential difference of 15 mV. It was found that the measured potential is sensitive to the Al mole fraction for AlGaAs. Two-dimensional delineation of Si-pn structures was successfully carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 7 publications
1
47
0
Order By: Relevance
“…The strength of KPFM is the capability to measure contact potential with a high spatial resolution, as demonstrated by imaging different materials [11], different doping in semiconductors [32] and localized charges [33]. Looking at the work function images in Figs.…”
Section: Lateral Variations In the Work Functionmentioning
confidence: 99%
“…The strength of KPFM is the capability to measure contact potential with a high spatial resolution, as demonstrated by imaging different materials [11], different doping in semiconductors [32] and localized charges [33]. Looking at the work function images in Figs.…”
Section: Lateral Variations In the Work Functionmentioning
confidence: 99%
“…For instance, KPFM has been utilized for the label-free detection of biomolecules [11,12] and for surface photovoltage measurements in optically active proteins [13]. Similarly, KPFM has been useful in mapping electrostatic potential profiles across working devices [14], surface photo-voltage in photovoltaics [15][16][17], and charging dynamics in ferroelectric [18][19][20] and dielectric materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…SPM has been successfully applied to semiconductor, 19 organic, 20 and ferroelectric 21,22 surfaces, as well as to defects, 23,24 and photoinduced 25,26 and thermal phenomena 27,28 in these materials. A number of SPM studies on grain boundary related phenomena have also been reported.…”
Section: Introductionmentioning
confidence: 99%